1992
DOI: 10.1101/gad.6.11.2201
|View full text |Cite
|
Sign up to set email alerts
|

The block to transcriptional elongation within the human c-myc gene is determined in the promoter-proximal region.

Abstract: A conditional block to transcriptional elongation is an important mechanism for regulating c-myc gene expression. This elongation block within the first c-myc exon was defined originally in mammalian cells by nuclear run-on transcription analyses. Subsequent oocyte injection and in vitro transcription analyses suggested that sequences near the end of the first c-myc exon are sites of attenuation and/or premature termination. We report here that the mapping of single stranded DNA in vivo with potassium permanga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
197
0
4

Year Published

1993
1993
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 249 publications
(216 citation statements)
references
References 59 publications
(62 reference statements)
15
197
0
4
Order By: Relevance
“…Additionally, evidence supporting some form of elongational control in specific vertebrate genes has existed since the early 1980s, for example, greater nuclear run-on signals from 59 portions than 39 regions of chicken b-globin 32 . Similar data for mammalian c-Myc and c-Fos were augmented with in vitro studies that suggested initially a termination control further downstream, but more thorough characterizations in vivo showed these genes to have properties like those of Drosophila Hsp70 paused Pol II 33,34 .…”
Section: How General Is Paused Pol Ii?supporting
confidence: 57%
“…Additionally, evidence supporting some form of elongational control in specific vertebrate genes has existed since the early 1980s, for example, greater nuclear run-on signals from 59 portions than 39 regions of chicken b-globin 32 . Similar data for mammalian c-Myc and c-Fos were augmented with in vitro studies that suggested initially a termination control further downstream, but more thorough characterizations in vivo showed these genes to have properties like those of Drosophila Hsp70 paused Pol II 33,34 .…”
Section: How General Is Paused Pol Ii?supporting
confidence: 57%
“…The c-myc gene can be expressed from four promoters (P0, P1, P2, P3), all of which appear to be regulated independently (Eick et al, 1990), with RNA initiated at the P2 promoter usually contributing 80-90% of total steady-state c-myc RNA in normal cells (Spencer and Groudine, 1991). RNA pol II pauses in the P2 promoter region, causing premature attenuation of P1 transcripts (Krumm et al, 1992), with the rate of RNA pol II release from the P2 pause site shown to regulate c-myc transcriptional activity (Strobl and Eick, 1992;Kohlhuber et al, 1993 resulted from P2 initiation alone, no increases in P1 transcript levels would have been observed. Our data therefore suggest that the enhanced c-myc mRNA levels observed after HGF/SF stimulation are mediated through both P1-and P2-initiated transcripts, following closely similar patterns of change.…”
Section: Discussionmentioning
confidence: 99%
“…Upon activation by heat shock, Pol II is able to rapidly transcribe these genes. Regulation of Pol II activity after recruitment has also been described in bacteria 23 , yeast 13 and mammalian cell lines 3,[6][7][8][9][10][11][12] , and includes instances where Pol II is found in an inactive pre-initiation complex 24,25 . We will collectively refer to inactive Pol II near the transcription start site as stalled Pol II.…”
mentioning
confidence: 95%